Challenges Faced by Migrant Students in Education: A Comprehensive Analysis of Legal, Psychological, and Economic Barriers - Khasanboy Abdusamatov; Dinara Babajanova; Dilshodjon Egamberdiev; Yunus Xodjiyev; Uktamjon Tukhtaev; Nodirbek Yusupov; Sitora Shoislomova (Qubahan Academic Journal)
This study aims to explore the multifaceted challenges faced by migrant students in educational settings, focusing on legal, psychological, and economic barriers. The research employs a mixed-methods approach, combining quantitative and qualitative data to provide a comprehensive analysis. A survey was conducted with 500 migrant students from various educational institutions across five countries, examining their experiences with legal, psychological, and economic challenges. In addition, 50 in-depth interviews with educators, policy makers, and migration experts were conducted to gain insights into systemic issues. The study revealed that migrant students face significant challenges across all three dimensions—legal, psychological, and economic. Over 60% of students in the study cited issues with residency permits, affecting their eligibility for financial aid, participation in extracurricular activities, and in some cases, their ability to enroll in school at all. Over 70% of the surveyed students reported experiencing social isolation, bullying, or discrimination in school environments. This negatively affected their academic performance and mental well-being. Financial instability was another prominent barrier, with 65% of the migrant students’ families reporting difficulty in affording school supplies, technology, or transportation to school. The study concludes that legal, psychological, and economic barriers significantly hinder the educational outcomes of migrant students. Legal documentation issues prevent many students from fully participating in educational programs, while psychological challenges such as social isolation and mental health struggles lead to poorer academic performance. Economic barriers exacerbate these issues by limiting access to necessary educational resources and support.